Meshing Performance Analysis of a Topologically Modified and Formed Internal Helical Gear Pair - Jianxin Su; Xiao Wei; Shilin Lian; Jiewei Xu (Machines)
Internal helical gear pairs are sensitive to manufacturing and assembly errors, loading deformation, which can result in vibration and noise. Three-dimensional topological modification of tooth surfaces is available to reduce this sensitivity. A 3D topological modification method is proposed by means of an internal helical gear form grinding method. The modified tooth surface model was constructed using spatial meshing theory and matrix transformations. Loaded tooth contact analysis (LTCA) was established to investigate the effect law of modification parameters on gear loading performance. Simulation results indicated that the contact area appeared at the middle area of the tooth surface under design loading conditions, with little edge contact existing. Transmission error decreased by up to 28.4% compared to the tooth without modification. The dynamic meshing performance of the internal helical gear pair was enhanced significantly. A transmission experiment was conducted to verify the effectiveness and validity of the simulation results.